FINANCIAL STRESS AND FARM INSECURITY AS PREDICTORS OF BURNOUT AMONG FARMERS IN RURAL COMMUNITIES IN RIVER STATE, NIGERIA - Emily, Emerhirhi (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Many factors, including the psychological condition of burnout, consistently threaten the contemporary agricultural ecosystem in Nigeria. The present study examined farmers' burnout based on financial stress and farming insecurities in a sample of farmers recruited from different farming communities in River state, Nigeria. Two hundred and fourteen respondents completed a self-report measure of financial stress, farming insecurity, and burnout. Two hypotheses were tested using data from the respondents. Multiple regression was performed on the data, and the result demonstrated a statistically significant effect of financial stress (?=186) and farming insecurity (?=167) on farmers' burnout. An observation of the R2 indicated that the predictor variables explained about 28.8% of the variation in farmer burnout. The result has implications for developing agricultural output and food security.